Are malignant self‐regard and vulnerable narcissism different constructs?. Issue 9 (6th March 2018) - Huprich, Steven K.; Nelson, Sharon; Sohnleitner, Aimee; Lengu, Ketrin; Shankar, Sneha; Rexer, Kyle
Abstract: In the clinical and empirical literature, vulnerable narcissism and malignant self‐regard (MSR) have been found to be highly interrelated and associated with theoretically related personality constructs, suggesting that the two constructs may be much more similar than different. The present study set out to test this hypothesis by examining the relationship of vulnerable narcissism and MSR to experiences and expressions of anger, the factor structure of grandiose and vulnerable narcissism with MSR, the associations of MSR and vulnerable narcissism to the five factor model of personality, and to global self‐esteem in self‐report measures within 1168 undergraduate students. A separate study of 158 undergraduates also assessed how MSR and vulnerable narcissism predicted state and trait anxiety and anger after receiving positive or negative feedback, and the extent to which negative feedback interacted with MSR and vulnerable narcissism. Overall, compared with grandiose narcissism, both MSR and vulnerable narcissism were more associated with experiencing anger internally, self‐reports of state and trait anger, high levels of neuroticism and openness, and lower levels of extraversion and global self‐esteem. Both vulnerable narcissism and MSR uniquely predicted trait levels of anger and anxiety and state levels of anger after receiving negative feedback. It is concluded that MSR and vulnerable narcissism are likely identical constructs.